PENGARUH KEPEMIMPINAN TRANSFORMASIONAL TERHADAP PRODUKTIVITAS KINERJA PEGAWAI PEMERINTAHAN YANG DIMEDIASI OLEH DISIPLIN SEBAGAI REGULATOR: (SYSTEMATIC REVIEW) - WD, Hendri Satria (Jurnal Widya Climago, 2022)
The productivity of an organization's performance in government can be influenced by various factors, one of the strongest factors that greatly influences the process of increasing or decreasing productivity, among others, comes from the leadership model and the application of discipline. This research was conducted using a systematic review method which aims to review published empirical research on transformational leadership that affects employee performance productivity and is mediated by discipline in government organizations. The data search strategy was carried out by a selection process from the Google Scholar, ProQuest, and Mendeley libraries. The study quality of the literature was assessed by analyzing the instrument, design and research results. The results of data extraction get the 10 best journals using the keywords transformational leadership, discipline, productivity, and governance. Based on a literature study that was systematically reviewed, the authors found that well-implemented transformational leadership can increase employee productivity in government through strengthening the application of discipline which is strongly influenced by leadership itself. So, it can be concluded that the hypothesis built in the study can be fulfilled.